2012
DOI: 10.3168/jds.2011-4309
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Mycoplasma bovis in Pennsylvania veal calves

Abstract: The objective of the study was to estimate the prevalence and incidence of Mycoplasma bovis, a common cause of pneumonia, in veal calves. Using simple random sampling, 252 calves from 4 veal herds located in central Pennsylvania were selected and longitudinally followed for monthly collection of nasal swabs. Bronchial swabs and lung lesions were collected at the slaughterhouse. Nasal, bronchial, and lung lesion swabs were cultured for bacterial respiratory pathogens. Ninety lung lesions were identified, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…Additionally, its role in the aetiology of bovine respiratory disease (BRD) is well known. In many cases, M. bovis is considered as a primary agent of BRD, which may co-infect with other infectious agents of BRD, such as Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and others (8,25). Houghton and Gourlay (11) reported that M. bovis is responsible for a colonising synergism with M. haemolytica, which may enhance morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, its role in the aetiology of bovine respiratory disease (BRD) is well known. In many cases, M. bovis is considered as a primary agent of BRD, which may co-infect with other infectious agents of BRD, such as Mannheimia haemolytica, Pasteurella multocida, Histophilus somni, and others (8,25). Houghton and Gourlay (11) reported that M. bovis is responsible for a colonising synergism with M. haemolytica, which may enhance morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Pardon et al (2013) found otitis and arthritis to represent 1.5% and 1.6% of the initial causes of antimicrobial treatment, which can be explained by a high prevalence of Mycoplasma bovis. M. bovis is highly prevalent among veal calves in Europe (Arcangioli et al, 2008;Radaelli et al, 2008;Pardon et al, 2013) and North America (Soehnlen et al, 2012). Recently, M. bovis has also been found in Danish veal calf herds (Nielsen, 2016) and may be responsible for a proportion of the treatments of joints/limbs/CNS and respiratory disorders in young calves.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of antibiotics and vaccines are not known to have negligible effects in calves [3] . Control of infection is difficult and economic loses is imminent [7,8] .…”
Section: öZetmentioning
confidence: 99%
“…Mycoplasma bovis-associated pneumonia occurs in cattle, including dairy and beef calves, beef cattle after arrival at a feedlot, and adults at any age [1] . Mycoplasma bovis is a particularly important cause of calf pneumonias [2,3] . Mycoplasma bovis infections can be explained as chronic and polymicrobial [1][2][3][4][5] .…”
Section: öZetmentioning
confidence: 99%
See 1 more Smart Citation